Synthesis and time resolved infrared analysis of photochemical oxiranyl carbene and diphenyl ketene precursors. Issue 43 (26th October 2016) - Tippmann, Eric M.; Curtis, Ryan
Graphical abstract: Highlights: Common synthesis of carbene precursor resistant to oxiranyl carbene precursors. Rearrangement mechanism formed a photochemical source of diphenylketene. The production of diphenylketene was determined by time-resolved spectroscopy. Abstract: Synthesis of a nonnitrogenous phenanthrene-based precursor of oxiranyl carbene yielded a photochemical source for diphenyl ketene after an in situ intramolecular rearrangement. The initial carbene precursor targeted rearranged from a putative spiro-oxiranyl intermediate to a cyclobutanone. Photolysis of the phenanthrene–cyclobutanone generated an infrared signal centered at 2100 cm −1 consistent with diphenyl ketene formation. Time-resolved infrared spectroscopy followed the reaction progress and measured bimolecular rate constants ( k obs = 9.1 × 10 6 M −1 s −1 ; butyl amine) consistent with diphenyl ketene formation. Quenching experiments combined with Stern–Volmer kinetics suggests a radical pathway is likely involved in the formation of diphenyl ketene from the phenanthrene-based precursor. The generality of the rearrangement is also discussed.